2017
DOI: 10.1104/pp.17.00934
|View full text |Cite
|
Sign up to set email alerts
|

Diacylglycerol Acyltransferase 1 Is Regulated by Its N-Terminal Domain in Response to Allosteric Effectors

Abstract: ORCID IDs: 0000-0001-8699-690X (R.J.W.); 0000-0003-4745-9153 (M.J.L.).Diacylglycerol acyltransferase 1 (DGAT1) is an integral membrane enzyme catalyzing the final and committed step in the acylcoenzyme A (CoA)-dependent biosynthesis of triacylglycerol (TAG). The biochemical regulation of TAG assembly remains one of the least understood areas of primary metabolism to date. Here, we report that the hydrophilic N-terminal domain of Brassica napus DGAT1 (BnaDGAT1 1-113 ) regulates activity based on acyl-CoA/CoA le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
66
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 45 publications
(73 citation statements)
references
References 65 publications
(81 reference statements)
6
66
1
Order By: Relevance
“…In addition, the N‐terminal region of B. napus DGAT1 formed dimers and tetramers based on crosslinking experiments (Weselake et al, ). Consistently, analysis of mouse and B. napus DGAT1 showed that the N‐terminal region plays a role in self‐oligomerization (Caldo et al, ; McFie et al, ). Furthermore, the hydrophilic N‐terminal region of B. napus DGAT1 was shown to constitute the enzyme's regulatory domain, which is not necessary for catalysis (Caldo et al, ).…”
Section: Introductionmentioning
confidence: 70%
See 4 more Smart Citations
“…In addition, the N‐terminal region of B. napus DGAT1 formed dimers and tetramers based on crosslinking experiments (Weselake et al, ). Consistently, analysis of mouse and B. napus DGAT1 showed that the N‐terminal region plays a role in self‐oligomerization (Caldo et al, ; McFie et al, ). Furthermore, the hydrophilic N‐terminal region of B. napus DGAT1 was shown to constitute the enzyme's regulatory domain, which is not necessary for catalysis (Caldo et al, ).…”
Section: Introductionmentioning
confidence: 70%
“…Consistently, analysis of mouse and B. napus DGAT1 showed that the N‐terminal region plays a role in self‐oligomerization (Caldo et al, ; McFie et al, ). Furthermore, the hydrophilic N‐terminal region of B. napus DGAT1 was shown to constitute the enzyme's regulatory domain, which is not necessary for catalysis (Caldo et al, ). This domain is comprised of two distinct segments, specifically an intrinsically disordered region (IDR) and a folded segment (Fig.…”
Section: Introductionmentioning
confidence: 70%
See 3 more Smart Citations